2018
DOI: 10.1007/s11207-018-1269-6
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter and X-Ray Emission from the 5 July 2012 Solar Flare

Abstract: The 5 July 2012 solar flare (11:39 -11:49 UT) with an increasing millimeter spectrum between 93 and 140 GHz is considered. We use space and ground-based observations in X-ray, extreme ultraviolet, microwave, and millimeter wave ranges obtained with the Reuven Ramaty High-Energy Solar Spectroscopic Imager, Solar Dynamics Observatory (SDO), Geostationary Operat ional E nvironmental Satellite, Radio Solar Telescope Network, and Bauman Moscow State Technical University millimeter radio telescope RT-7.5. The main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…In the last panel of figure 1, we showed the centimeter microwave measurements from RSTN (Radio Solar Telescope Network,San vito) at 1.4,2.7,4.9,8.8 and 15.4 GHz (Guidice et al 1981;Tsap et al 2018). The radio emission at 1.4GHz has a rather lower flux density than those at higher frequencies during the X9.3 flare, the pattern of 2.7 GHz flux showed several impulsive peaks during the impulsive phase.…”
Section: Observationsmentioning
confidence: 99%
“…In the last panel of figure 1, we showed the centimeter microwave measurements from RSTN (Radio Solar Telescope Network,San vito) at 1.4,2.7,4.9,8.8 and 15.4 GHz (Guidice et al 1981;Tsap et al 2018). The radio emission at 1.4GHz has a rather lower flux density than those at higher frequencies during the X9.3 flare, the pattern of 2.7 GHz flux showed several impulsive peaks during the impulsive phase.…”
Section: Observationsmentioning
confidence: 99%
“…The literature is vast and selected references will be provided in sections 6.2-6.4, primarily for publications that link modeling of gyrosynchrotron emission with observations. Gyrosynchrotron radiation can also be detected at millimeter wavelengths and is produced by electrons with energies of more than 1 MeV (e.g., White and Kundu, 1992;Kundu et al, 1994;Silva et al, 1996;Raulin et al, 1999;Silva and Valio, 2016;Tsap et al, 2018). (2) Weak transient brightenings, when observed at microwaves, may sometimes show emission consistent with the properties of gyrosynchrotron radiation (e.g., Gary et al, 1997;Krucker et al, 1997;Nindos et al, 1999;Kundu et al, 2006).…”
Section: General Remarksmentioning
confidence: 99%
“…They also observed that 345 GHz is optically thick and should come from a lower height. In our case, if the emission were optically thick gyrosynchrotron, the spectral index between 212 and 405 GHz, α ≃ 0.8, would indicate an inhomogeneous source (Klein & Trottet, ; Simões & Costa, ), while Tsap et al () propose a mixture of gyrosynchrotron and thermal bremsstrahlung absorption to explain the spectral increase between 93 and 140 GHz during SOL2012‐07‐05T11:44. The mid‐IR flux can be explained, as in Trottet et al (), as optically thin thermal bremsstrahlung emission of a heated chromospheric plasma, since fluxes of the two events are similar.…”
Section: Discussionmentioning
confidence: 58%